▼Dronedarone for atrial fibrillation?. Issue 11 (5th November 2010) - Unknown
Abstract : Atrial fibrillation (AF) is the commonest sustained heart arrhythmia and is associated with significant morbidity and mortality, with, for example, one in five of all strokes being attributable to the condition.1 ▼Dronedarone (pronounced dro- ne -da-roan) (Multaq – sanofi-aventis) is a new anti-arrhythmic drug related to the established anti-arrhythmic amiodarone. It is licensed for use in clinically stable adult patients with a history of, or current, non-permanent AF to prevent recurrence of AF or to lower ventricular rate. Here we review its role in the management of patients with non-permanent AF.